Cultural Ecology of Asante: 1702 - 1945 - Boakye-Boateng, A. (University of Ghana, 1974)
The present can be considered as the product of the past" The truth of the statement is demonstrated in a study like this one which uses the genetic approach. Such an approach makes it possible for the present to be illuminated by the past: thus making it possible to explain many of the elements in the environment. This study on Asante reveals that the region had passed through two major socio-economic phases since the formation of the Asante Confederacy in about 1702. The date 1702, therefore, marks me beginning of the first phase which ends In 1901. During this phase the dominant force (theme) which controlled the cultural ecology was the Asante political power. The Asante Court controlled the main economic activities, namely, trade and gold mining; as well as me various crafts, such as goldsmithing, cire purdue metal casting, cloth making wood carving. The Court also controlled the population growth and distribution. Unfornmately, agriculture was not considered an important economic venture, therefore, it did not form part of the Court's delliberations. The Asante political power did not flourish forever. In 1902 this power oollapsed completely and Asante annexed to the British Crown. This saw the beginning of the second phase. This phase was characterized by the establishment of Pax Britanica. Within this peaceful atmosphere the cultivation of cocoa was encouraged. This was the era of commercial agriculture. It was this innovation which made all the difference in the cultural ecology of Asante. The processes In this phase ushered Asante into the contemporary by 1945. Indeed, by this date, it was clear that the basic characteristics of the contemporary cultural ecology were sketched. The various elements that make each phase distinctive have been treated with the view of showing both developments and changes that occurred.
PhD. Historical Geography
Keywords: Asante; Political Power; Court; Cultural Ecology